Bacterial leakage in root canals filled with resin-based and mineral trioxide aggregate-based sealers - Hamid Razavian; Behnaz Barekatain; Elham Shadmehr; Mahdieh Khatami; Fahime Bagheri; Fariba Heidari (Wolters Kluwer Medknow Publications, 2014)
Background: Sealing ability is one of the most important features of endodontic sealers. The purpose of this in vitro study was to compare the sealing ability of a resin-based sealer with a mineral trioxide aggregate-based sealer. Materials and Methods: A total of 60 single-rooted extracted human teeth were randomly divided into two experimental groups (n = 25) and two control groups (n = 5). After canal preparation and smear layer removal, both groups were obturated with gutta-percha and sealer. Resin-based AH26 sealer was used in the first group and Fillapex ® sealer in the second group. Two layers of nail varnish were applied on tooth surfaces except for the apical 2 mm. In the negative control group, nail varnish was applied on the entire surface. The teeth were mounted according to Lima et al. study and then sterilized by ethylene oxide gas. The samples were evaluated for bacterial microleakage using Enterococcus faecalis (ATCC 29212) for 90 days. Data were analyzed by survival test (P < 0.05). Results: Control groups had either immediate leakage or no leakage. The Fillapex ® showed significantly higher amounts of microleakage compared with AH26 sealer (P < 0.05) and both groups exhibited significant differences in comparison with control groups. Conclusion: Both sealers had bacterial leakage. Sealing ability of AH26 was significantly higher than that of Fillapex ® .